2018
DOI: 10.1037/xlm0000519
|View full text |Cite
|
Sign up to set email alerts
|

The misinterpretation of noncanonical sentences revisited.

Abstract: Most current models of sentence comprehension assume that the human parsing mechanism (HPM) algorithmically computes detailed syntactic representations as basis for extracting sentence meaning. These models share the assumption that the representations computed by the HPM accurately reflect the linguistic input. This assumption has been challenged by Ferreira (2003), who showed that comprehenders sometimes misinterpret unambiguous sentences in which subject and object appear in noncanonical order, such as pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
78
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(101 citation statements)
references
References 77 publications
18
78
4
Order By: Relevance
“…This is contradictory to previous findings suggesting preceding contexts influence offline representations (Christianson & Luke, 2011;Grodner et al, 2005 respectively), and we suggest that the difference is telling about how task instructions influence subsequent reading of text. An alternative account of lingering misinterpretations is that they arise due to postinterpretive processes (Bader & Meng, 2018) because question accuracy does not veridically measure the quality of sentence-final interpretations but rather reveals artifacts of the memory retrieval process imposed by metalinguistic tasks. While offline tasks play an important role in psycholinguistic inquiry (see Ferreira & Yang, 2019 for an excellent review), it is true that comprehension questions may elicit artifacts derived from recalling linguistic representations.…”
Section: Discussionmentioning
confidence: 99%
“…This is contradictory to previous findings suggesting preceding contexts influence offline representations (Christianson & Luke, 2011;Grodner et al, 2005 respectively), and we suggest that the difference is telling about how task instructions influence subsequent reading of text. An alternative account of lingering misinterpretations is that they arise due to postinterpretive processes (Bader & Meng, 2018) because question accuracy does not veridically measure the quality of sentence-final interpretations but rather reveals artifacts of the memory retrieval process imposed by metalinguistic tasks. While offline tasks play an important role in psycholinguistic inquiry (see Ferreira & Yang, 2019 for an excellent review), it is true that comprehension questions may elicit artifacts derived from recalling linguistic representations.…”
Section: Discussionmentioning
confidence: 99%
“…An account that emphasises postinterpretive processes as main sources of misinterpretation effects has been proposed in Bader and Meng (2018). The account is based on two experiments that investigated unambiguous noncanonical sentences in German.…”
Section: Introductionmentioning
confidence: 99%
“…To capture the differences between agent/patient naming and plausibility judgements, Bader and Meng (2018) proposed the retrieval account of misinterpretation errors . According to this account, misinterpretation errors with agent/patient naming reflect task-specific processes, in particular, the need to retrieve information from the sentence representation after some delay.…”
Section: Introductionmentioning
confidence: 99%
“…Although we believe that checking participants' interpretations of agreement attraction sentences is crucial to disentangling the encoding-and retrieval-based accounts, there is a significant caveat to using comprehension questions: One cannot be certain that the given answer matches the thematic relations computed during the online processing of the sentence (see also Schlueter et al, 2019). Bader and Meng (2018) have recently argued that answers to comprehension questions may be the result of what Caplan and Waters (1999) call post-interpretive processing (see also Paolazzi, Grillo, Alexiadou, & Santi, 2019). Caplan and Waters argue that the parser generates a syntactic structure and assigns meaning to the sentence online (interpretive processing), but that afterwards additional processes come into play whose output does not always match the online interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Caplan and Waters argue that the parser generates a syntactic structure and assigns meaning to the sentence online (interpretive processing), but that afterwards additional processes come into play whose output does not always match the online interpretation. As a case in point, Bader and Meng (2018) tested implausible passive sentences such as The chef was cleaned by the pan. They found that participants often made errors when they were asked to name the agent of such sentences, but that they were highly accurate when evaluating their plausibility in a speeded task.…”
Section: Discussionmentioning
confidence: 99%